2012
DOI: 10.1100/2012/358102
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Angiotensin Type 1 and Type 2 Receptors in Estrogen-Induced Cell Proliferation and Vascular Endothelial Growth Factor Expression in the Rat Anterior Pituitary

Abstract: The aim of our study was to examine the involvement of renin-angiotensin system (RAS) in estrogen-induced lactotropes proliferation and vascular endothelial growth factor (VEGF) expression in rat pituitary. The study was performed on Fisher 344 rats underwent 8-day treatment with diethylstilboestrol (DES). The proliferation index (PCNA) and VEGF expression in pituitary sections were estimated using immunohistochemical methods. Treatment with DES increased the number of PCNA-positive cells, VEGF-positive cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…On the other hand, Lawnicka et al noticed that stimulation of proliferation in rat anterior pituitary by diethylstilboestrol (DES), synthetic estrogen, was inhibited by losartan (AT1R antagonist), PD123319 (AT2R antagonist), and captopril (ACE inhibitor). This result was evidence of AT1R and AT2R involvement in estrogen-dependent mitogenic effect in rat pituitary [54]. Surprisingly, the research carried out by Ptasinska-Wnuk et al revealed anti-proliferative consequence of angiotensins [Ang II, Ang IV, angiotensin 5-8 (Ang 5-8)] on GH3 lactosomatotroph pituitary tumor cell culture.…”
Section: Pituitary Glandmentioning
confidence: 89%
See 3 more Smart Citations
“…On the other hand, Lawnicka et al noticed that stimulation of proliferation in rat anterior pituitary by diethylstilboestrol (DES), synthetic estrogen, was inhibited by losartan (AT1R antagonist), PD123319 (AT2R antagonist), and captopril (ACE inhibitor). This result was evidence of AT1R and AT2R involvement in estrogen-dependent mitogenic effect in rat pituitary [54]. Surprisingly, the research carried out by Ptasinska-Wnuk et al revealed anti-proliferative consequence of angiotensins [Ang II, Ang IV, angiotensin 5-8 (Ang 5-8)] on GH3 lactosomatotroph pituitary tumor cell culture.…”
Section: Pituitary Glandmentioning
confidence: 89%
“…Many studies revealed correlation between angiotensin and proliferation of pituitary gland cells [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Moreover, Ang II was observed to induce proliferation of mouse spleen lymphocytes in vitro.…”
Section: Pituitary Glandmentioning
confidence: 99%
See 2 more Smart Citations
“…** P<0.01 compared with Control group and Telmisartan group(one-way ANOVA). [20][21][22]. Besides, angiogenesis might be another reason.…”
Section: Pulmonary Arterial Wall Thickness and Elastic Fibersmentioning
confidence: 99%